Mobilization of Savings in Eastern European Countries : The Role of the State - Tanzi, Vito (IMF Working Papers; Working Paper, 1991)
As the countries of Eastern and Central Europe transform their economies from centrally-planned to market-oriented, the question of the role that the governments should play in mobilizing savings to ensure a high growth rate must be addressed. This paper argues that the issue of a good allocation of savings must precede that of mobilization. Much evidence suggests that major distortions have, in the past, dramatically reduced the productivity of investment. The paper discusses some of the institutional changes that will be necessary to ensure a better allocation of savings.